2023
DOI: 10.1002/adma.202306765
|View full text |Cite
|
Sign up to set email alerts
|

Facile Photopatterning of Perfusable Microchannels in Synthetic Hydrogels to Recreate Microphysiological Environments

Ana Mora‐Boza,
Adriana Mulero‐Russe,
Nikolas Di Caprio
et al.

Abstract: The fabrication of perfusable hydrogels is crucial for recreating in vitro microphysiological environments. Existing strategies to fabricate complex microchannels in hydrogels involve sophisticated equipment/techniques. We report a cost‐effective, facile, versatile, and ultra‐fast methodology to fabricate perfusable microchannels of complex shapes in photopolymerizable hydrogels without the need of specialized equipment or sophisticated protocols. Our methodology utilizes one‐step UV light‐triggered crosslinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…An added value of this treatment is the fact that it is possible to reproduce complex geometries using a simpler manufacturing method than photopatterning 40,43 with the ability to create a variety of designs, and, what's more, with total channel-to-channel contact that the phaseguide technique 38,39 containing a step does not give. With this surface treatment, it is possible to design more precise geometries that simulate more realistic tissues or histological structures, reproducing not only the shape but also the shear forces under flow conditions.…”
Section: Customizable Hydrogel Patterns In Pillarless Microfluidic De...mentioning
confidence: 99%
See 1 more Smart Citation
“…An added value of this treatment is the fact that it is possible to reproduce complex geometries using a simpler manufacturing method than photopatterning 40,43 with the ability to create a variety of designs, and, what's more, with total channel-to-channel contact that the phaseguide technique 38,39 containing a step does not give. With this surface treatment, it is possible to design more precise geometries that simulate more realistic tissues or histological structures, reproducing not only the shape but also the shear forces under flow conditions.…”
Section: Customizable Hydrogel Patterns In Pillarless Microfluidic De...mentioning
confidence: 99%
“…[33][34][35][36] Another pillar free design is the phaseguide technology which consists of meniscus pinning barriers, [37][38][39] but this technique does not allow the possibility of designing any geometry. Photopatternable hydrogels, [40][41][42][43] although representing a cutting-edge technology, present a challenge due to the complex development and manipulation required, despite their capability to achieve highly varied designs and geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding islands of gel were photopatterned inside a simple microfluidic flow cell (Fig 3a), following procedures previously described by us and others. 4,30 The chip was filled with fluorescently labeled polymer precursor solution, a photomask laid over the chip, and the precursor exposed through a 800 µm diameter pinhole. This simple photopatterning strategy made it straightforward to evaluate multiple exposure times on a single chip, by exposing one region, re-positioning the mask, re-exposing, and so on (Fig.…”
Section: Stability Of Gelma Features Was Related Sigmoidally To Docmentioning
confidence: 99%
“…3,7,8 Similarly, cell-laden hydrogel constructs have been photopatterned with precise spatial and temporal control by lithography through a mask to mimic the complex architecture and local microenvironments of organs in vivo. [9][10][11] While studies have reported successful culture of encapsulated cell lines [12][13][14][15] and induced pluripotent stem cells [16][17][18] within photocrosslinked hydrogels and 3D printed scaffolds, there is also evidence of photoreaction-induced damage to a host of cell types. Exposure to ultraviolet radiation, photoinitiator and the highly reactive free radicals generated during photocrosslinking could damage plasma membranes, DNA and proteins, causing harm to cells and impairing cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,8 Similarly, cell-laden hydrogel constructs have been photopatterned with precise spatial and temporal control by lithography through a mask to mimic the complex architecture and local microenvironments of organs in vivo. [9][10][11] (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%